2018
DOI: 10.1016/j.carbpol.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronate coating enhances the delivery and biocompatibility of gold nanoparticles

Abstract: For targeted delivery with nanoparticles (NPs) as drug carriers, it is imperative that the NPs are internalized into the targeted cell. Surface properties of NPs influence their interactions with cells. We examined the responses of retinal pigment epithelial cells, NIH 3T3 fibroblast cells, and Chinese hamster ovary cells to gold nanoparticles (Au NPs) in their nascent form as well as coated with end-thiolated hyaluronate (HS-HA). The grafting density of HS-HA on Au NPs was calculated based on total organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…Because GNPs have shown antiangiogenic and antioxidant effects (Arvizo et al, 2011;Roh et al, 2016), long-term stability, and long residence times in tissues (Cho et al, 2010), we considered the possibility that HA-coated GNPs might not only allow targeted transport of specific drugs and enhancement of the uptake via CD44 receptor, but also cause non-toxic, synergistic effects between carrier and drug. It has been shown that HA-coating is able to mitigate GNPs toxicity increasing their biocompatibility as a free-radical quencher (Karakocak et al, 2018). Thus, as a proof-of-concept, we tested the protective and antioxidant properties of GNPs and HA-GNPs against AGEs under hyperglycaemic conditions in ARPE-19 cells (Kowluru, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because GNPs have shown antiangiogenic and antioxidant effects (Arvizo et al, 2011;Roh et al, 2016), long-term stability, and long residence times in tissues (Cho et al, 2010), we considered the possibility that HA-coated GNPs might not only allow targeted transport of specific drugs and enhancement of the uptake via CD44 receptor, but also cause non-toxic, synergistic effects between carrier and drug. It has been shown that HA-coating is able to mitigate GNPs toxicity increasing their biocompatibility as a free-radical quencher (Karakocak et al, 2018). Thus, as a proof-of-concept, we tested the protective and antioxidant properties of GNPs and HA-GNPs against AGEs under hyperglycaemic conditions in ARPE-19 cells (Kowluru, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the experimental endpoint toxicity evaluations of viability, apoptosis, and ROS generation, electrical impedance spectroscopy (ECIS), a sensing technique for monitoring cell motion and morphological changes real-time, was also used 45,46 . Upon plating, cells start to attach to and spread out over the gold electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the stronger interactions of GNPs with a positive surface charge with the cell membrane and resulting membrane damage. In a comprehensive study by our group, we reported that surface properties of bionanomaterials, such as surface chemistry and surface charge, significantly affect cellular behaviors.43 A study by Karakocak et al demonstrated that surface modification of GNPs and changes in surface chemistry strongly affect cell uptake and subsequently cellular behavior.44 They found that the native 50 and 100 nm GNPs could not enter the cell whereas that GNPs coated with end-thiolated hyaluronate facilitated their entry in the cells through CD44 receptors that in turn resulted in a greater payload of the drug to cells.44…”
Section: Discussionmentioning
confidence: 99%